The Recursive Symbiosis of Spiritual Experience and Local Wisdom: A Phenomenological Inquiry into the Post-Reservoir Construction Cipeundeuy Community - Engkos Koswara; Moh Anif Arifani; Ismail Lamdoh (Al-Albab, 2026)
The construction of the Cirata Reservoir fundamentally restructured the geographic and socio-economic profile of the Cipeundeuy community, forcing a rapid transition from a terrestrial agrarian society to an aquatic-centered ecosystem. This study investigates the resulting tension and synergy between individual spiritual experiences and collective local wisdom within this transitional landscape. Utilizing a mixed-methods approach grounded in field data, the research applies a theoretical synthesis of Symbolic Interactionism and Bourdieu’s concept of Habitus to analyze cultural adaptation. Results indicate a significant “institutionalization of the ineffable,” where the majority of respondents reported new transcendental states only after joining local Majlis Taklim (religious assembly), positioning these assemblies as “spiritual incubators” that provide a new semiotic framework for mystical encounters. Simultaneously, the data reveals a state of “normative fragmentation” regarding ancestral taboos (pamali), reflecting a habitus in flux as it encounters modern structural demands. The discussion posits that the community exhibits “Prismatic Resilience,” characterized by a recursive symbiosis: spiritual experiences provide the internal vitality to sustain cultural traditions, while local wisdom offers the necessary grammar to articulate these experiences. Ultimately, the survival of Cipeundeuy’s identity amidst displacement is contingent upon the mutual preservation of subjective mystical encounters and ancestral symbolic frameworks.